2020
DOI: 10.1111/ecog.05032
|View full text |Cite
|
Sign up to set email alerts
|

Biotic interactions hold the key to understanding metacommunity organisation

Abstract: Biotic interactions are fundamental drivers governing biodiversity locally, yet their effects on geographical variation in community composition (i.e. incidence‐based) and community structure (i.e. abundance‐based) at regional scales remain controversial. Ecologists have only recently started to integrate different types of biotic interactions into community assembly in a spatial context, a theme that merits further empirical quantification. Here, we applied partial correlation networks to infer the strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 59 publications
2
79
1
1
Order By: Relevance
“…Additionally, as mentioned above, macroinvertebrates are a dispersal vector for diatoms, which could lead to cooccurrence. However, co-variation between two groups of taxa, as in our results, could also be caused by responses to abiotic filtering (Zhao et al, 2019;García-Girón et al, 2020) not examined in this study. Previous studies have found that in addition to abiotic factors, like landscape structure and local environmental conditions, biotic interactions can significantly shape metacommunities.…”
Section: Influence Of Connectivity On Dispersal and Metacommunitiesmentioning
confidence: 55%
See 2 more Smart Citations
“…Additionally, as mentioned above, macroinvertebrates are a dispersal vector for diatoms, which could lead to cooccurrence. However, co-variation between two groups of taxa, as in our results, could also be caused by responses to abiotic filtering (Zhao et al, 2019;García-Girón et al, 2020) not examined in this study. Previous studies have found that in addition to abiotic factors, like landscape structure and local environmental conditions, biotic interactions can significantly shape metacommunities.…”
Section: Influence Of Connectivity On Dispersal and Metacommunitiesmentioning
confidence: 55%
“…Previous studies have found that in addition to abiotic factors, like landscape structure and local environmental conditions, biotic interactions can significantly shape metacommunities. For example, macrophyte communities were found to structure filter-feeding zooplankton and predacious macroinvertebrate communities in pond ecosystems (García-Girón et al, 2020). However, we found that when comparing the whole range to the common zone, the association between macroinvertebrate and diatom community dissimilarity is no longer significant.…”
Section: Influence Of Connectivity On Dispersal and Metacommunitiesmentioning
confidence: 60%
See 1 more Smart Citation
“…For example, biotic interactions such as predation, competition, facilitation, etc. seem to play an important role structuring metacommunities, increasing the influence of environment (both abiotic and biotic) on metacommunity assembly (Leibold and Chase, 2018;García-Girón et al, 2020). Furthermore, ecological drift, or random variation of species abundances, generating differences between sites, is also a strong process influencing metacommunity structure and dynamics (Jeffries, 1988;Chase, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the statistical methods used might not be the best for the data being analyzed (e.g., linear models for non-linear environmental responses), although recent studies have developed new and promising methods (Clappe et al, 2018;. Moreover, the large unexplained variation in empirical data demonstrates multiple and complex variation sources largely disregarded in the simulations, such as methodological errors when sampling or processing the samples, the influence of rare species (Magurran and Henderson, 2003) or trophic interactions (Guzman et al, 2019;García-Girón et al, 2020).…”
Section: Discussionmentioning
confidence: 99%